The Masonic Activities of the First Rector of Yerevan State University Y.S. Ghambaryan - Movsisyan, Felix (History and Culture, 2025)
The Masonic activities of Yuri Stepan Ghambaryan (Ghambarov), the first rector of Yerevan State University, hasn’t been fully studied by Armenian historiography. The fact of his becoming a freemason and his activities were closely related to M.M. Kovalevski who was a famous Russian historian, jurist, sociologist, ethnographer, public and political figure. On May 16, 1905, in Paris Lodge No.288, under the guidance of M.M. Kovalevski, Y.S. Ghambaryan was ordained a First Degree Mason, On January 30, 1906, he was ordained a Second and then a Third Degree Mason in the "Cosmos" Lodge No.288, which rarely happened in freemasonry. He remained a member of that lodge until 1908, although he returned to Petersburg in August, 1906. On November, 1906, M.M. Kovalevsky founded the first lodge of Russian Political freemasonry "Polar Star" in Petersburg and Y.S. Ghambaryan joined it at the beginning of 1907. In 1906 in Petersburg Ghambaryan became one of the five main members of the "Phoenix" Lodge founded by Kovalevsky. On May 8, 1908, M.M. Kovalevsky, Y.S. Ghambaryan and their associates left the "Polar Star" Lodge because of disagreements with the leaders of the Moscow "Liberation" Lodge and founded their own "Cosmos" Lodge which didn’t function for long. In summer 1912, Y.S. Ghambaryan became a member of the masonic organization "Great East of the Peoples of Russia" in Moscow. During the period of politicization of Freemasonry in Russia, Y.S. Ghambaryan wasn’t active in masonic activities, as far as he wasn’t a member of any political party and wasn’t engaged in politics either. From that moment until the end of his life, he was engaged exclusively in professional and scientific activities.